PELAKSANAAN PIDANA DENDA DALAM PERKARA TILANG KENDARAAN BERMOTOR DI PENGADILAN NEGERI KELAS 1A SAMARINDA - Busyiri Busyiri (Universitas 17 Agustus 1945 Samarinda, 2021)
AbstractTraffic violations in the City of Samarinda are increasing because of the lack of awareness of road users about driving rules. In general, there are still many people who do not know about the process of ticketing cases in Samarinda District Court. The purpose of this study was to determine the trial process of traffic violations in Samarinda District Court, to find out the Judges' considerations in passing a fine decision on a ticket case and to know the decision on a fine in a ticket case, whether or not an appeal was made according to Law Number 22 of 2009 concerning Traffic and road transport. The research method used in this study is the Juridical Empirical and Normative Juridical where research data are sourced from primary, secondary and tertiary data. The results of the study revealed that the trial proceedings at the Samarinda District Court were carried out by a quick examination and the offenders were subject to criminal sanctions based on court decisions. It is known that the Judge's consideration in imposing a fine verdict on a speeding case explains that the Judge already has a data table on traffic violations regarding the amount of the fine to be imposed based on the violation article and the court's determination regarding traffic violations in the form of criminal fines cannot be appealed yet but if the decision is in the form of deprivation of liberty or imprisonment, an appeal can be filed according to the provisions in Article 214 paragraph (4) of the Criminal Procedure Code.